WSPIERANIE MAŁYCH I ŚREDNICH PRZEDSIĘBIORCÓW - CHARAKTERYSTYKA PRZEPISÓW PRAWA DZIAŁALNOŚCI GOSPODARCZEJ I ICH REALIZACJA - Popowska, Bożena (Wydział Prawa i Administracji UAM, 2002)
On the basis o f the European Commission recommendations the Polish Business Activity Law Act introduced new notions into the economic legislation. The notions of small and medium-sized entrepreneur were introduced in order for the entrepreneurs to be treated in a special way, namely, new legal regulations will be addressed to them and other actions will be taken for their benefit. This special treatment would consist in creating new favourable conditions, in which small and medium-sized entrepreneurs will operate. In the light of the Business Activity Law, the State is responsible for creating these conditions and thus supporting small and medium-sized entrepreneurs. The way in which the above mentioned responsibility is formulated, is characteristic of the category of programme standards included in the theory o f law. The support for SMEs consists mainly in non-imperative and factual actions (training, informative, and promotional actions) but also legal actions (equalising the conditions of conducting a business activity with respect to the obligations under the public law). Among the new institutions which support entrepreneurship, the Polish Entrepreneurship Development Agency should be mentioned in the first place. The aim of the Agency is to participate in the implementation o f the economic development programmes, especially in the area of support for small and medium-sized entrepreneurs. The Agency operates almost on the entire state territory mentioned in article 53 of the Business Activity Law Act. Numerous new legal solutions are also designed to support entrepreneurship. These solutions are beneficial to small and medium-sized entrepreneurs and include, for example, limitation of the obligations concerning accountancy and reporting. Determining the new requirements concerning participation in the public orders, which are easier to fulfil than the previous requirements, may serve as another example. Judging by the above examples, it appears that the solutions aimed at supporting entrepreneurship do not necessarily discriminate against other entrepreneurs and will not necessarily have a negative impact on competition. In this respect the support of entrepreneurship as regulated by the Business Activity Law differs fundamentally from the actions carried out within the public aid framework.
SUPPORTING SMALL AND MEDIUM-SIZED ENTREPRENEURS - A DESCRIPTION OF THE PROVISIONS OF THE BUSINESS ACTIVITY LAW AND THEIR IMPLEMENTATION